Think Talk Write Strategy on Economics Subject - Yunikawati, Nur Anita (Classroom Action Research Journal (CARJO), 2017)
AbstractÂ This research was conducted in order to determine how the application of learning technic Think Talk Write (TTW) on activity and learning outcomes of student in economic subjects x IIS 3 in SMA Laboratorium UM. This research uses qualitative approach by class action research, which was done in 2 cycles. Every cycle consists of 3 meetings through 4 steps, that is planning, doing, observing, and reflecting. The subject of this research is students of X IIS 3 that consists of 32 students. Based on the results of the study, it showed that the enforceability of the implementation of the Think Talk Write (TTW) technic has increased from the first cycle that was 83% to 93% in the second cycle. The student's activity increased from the first cycle of 67,79% to 81,27% in the second cycle. Cognitive aspects of learning outcomes of a student in the first cycle of 25% with an average value of 60 increased by 100% with an average value of 86. From this analysis, it is concluded from the results that the feasibility study technic Think Talk Write (TTW) on The students activity and learning outcomes of students increased in the second cycle compared to the first cycle that is very appropriate implementation of learning applied to economic subject for the X grade students of Social Studies 3 in SMA Laboratorium UM.Keyword: Think Talk Write, Activity, Learning OutcomeDOI:Â 10.17977/um013v1i12017p028